Forming clusters within clusters: how 30 Doradus recollapsed and gave birth again - Rahner, Daniel; Pellegrini, Eric William; Glover, Simon; Klessen, Ralf S. (Monthly notices of the Royal Astronomical Society. Letters, 2018)
Abstract. The 30 Doradus nebula in the Large Magellanic Cloud (LMC) contains the massive starburst cluster NGC 2070 with a massive and probably younger stellar
Advance access publication 2017 September 22
Gesehen am 02.04.2019